Revisiting the 1993 Extreme Precipitation in Central Nepal: Synoptic Feature and Numerical Simulation - Pokharel, Binod; Hamal, Kalpana; Zhao, Lin; Aryal, Deepak; Rajbhandari, Dharmendra Prakash; Marahatta, Suresh; Sharma, Shankar (Jalawaayu, 2022)
The cloudburst event occurred on 19-20 July 1993, creating a devastating flash flood over south-central Nepal. The storm killed hundreds of people, and damaged millions of dollars of properties. This study focused on the synoptic and thermodynamics that triggered the cloudburst in central Nepal, bringing 540 mm of rainfall over a small region in less than 24 hours. Moreover, it investigates the primary reason for the particular extremest event in Nepal. Our results show the strong upward motion transported the significant moisture that led to favorable condition for development of thick cloud cover, producing a record-breaking precipitation during that event over central Nepal. Likewise, the monsoon trough with negative sea level pressure anomaly over central Nepal located east of the upper-level trough further suggests a westward tilt with height in the disturbances associated with cloudburst on the event day. Further, we also simulate the extreme precipitation events over the region using Weather Research Forecast (WRF) model however, it underestimated the precipitation amount with slight shift in event location. The model simulates the actual thermodynamics, but it fails to produce the actual precipitation. Moreover, it is difficult to simulate the actual topography over the complex region where orography plays an essential role in producing high precipitation.